Highly compartmentalized microbiomes in blueberry microhabitats - Giese, Matteo; Stefani, Erika; Larger, Simone; Pindo, Massimo; Farneti, Brian; Ajelli, Matteo; Cattani, Monica; Delgado-Baquerizo, Manuel; Coleine, Claudia; Donati, Claudio (Frontiers in Microbiology, 2026)
IntroductionBlueberries are considered a superfood because of their rich content of vitamins, antioxidants, and fiber, supporting multiple health benefits. Plants host complex microbiomes that play crucial roles in resistance to pathogens, productivity, and stress tolerance. Despite its importance, a comprehensive characterization of the microbiota across all major compartments of cultivated blueberry (Vaccinium corymbosum) is still lacking.MethodsUsing high-throughput sequencing of marker genes, we provide the first integrative survey of fungal and bacterial communities associated with three distinct plant compartments: rhizosphere, leaf surface, and fruit surface, as well as the bulk soil, across 100 samples, generating datasets of over 4,000 unique fungal and 38,000 unique bacterial amplicon sequence variants (ASVs).ResultsWe found clear compartment differentiation, with pronounced shifts in richness, diversity, and taxonomic composition between belowground and aboveground compartments. Alpha diversity peaked in bulk soils and declined progressively toward aboveground tissues. We further detected minimal overlap across compartments, with only 9 fungal and 12 bacterial ASVs shared across all compartments. These findings challenge the soil-origin hypothesis for aboveground microbiota.ConclusionBlueberry plants harbor highly compartmentalized microbial communities shaped by selective environmental and physiological filtering. Our findings provide a baseline for future development of targeted, compartment-specific bioinoculants aimed at enhancing beneficial microorganisms for blueberry cultivation.